2018
DOI: 10.1016/j.physb.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SnS addition on the morphological and optical properties of (SnS)m(Sb2S3)n nano-rods elaborated by glancing angle deposition

Abstract: (SnS) m (Sb 2 S 3) n thin films were prepared by thermal evaporation using the glancing angle deposition technique (GLAD). The incident angle between the particle flux and the normal to the substrate was fixed at 80°. The Raman and XRD characterization revealed the amorphous character of the films due to the columnar structure as shown by the SEM characterization and AFM analysis. A strong change of the surface morphology of the films was observed and it depends on the composition. Optical properties were extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…From the linear regression analysis, the E g values were calculated, which are in the range of 1.63 and 1.80 eV (see Table 2). These values are in agreement with the reported in the literature (Larbi et al, 2014b andAbdelkader et al, 2018). Plots of (αhν) 2 or (αhν) 1/2 versus hν brings down the correlation factor to 0.96 or less, making the straight-line fit unacceptable, i. e., the linear fit establishes that the direct forbidden electronic transitions take place during the optical absorption (Smith, 1978).…”
Section: Optical Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…From the linear regression analysis, the E g values were calculated, which are in the range of 1.63 and 1.80 eV (see Table 2). These values are in agreement with the reported in the literature (Larbi et al, 2014b andAbdelkader et al, 2018). Plots of (αhν) 2 or (αhν) 1/2 versus hν brings down the correlation factor to 0.96 or less, making the straight-line fit unacceptable, i. e., the linear fit establishes that the direct forbidden electronic transitions take place during the optical absorption (Smith, 1978).…”
Section: Optical Propertiessupporting
confidence: 90%
“…The same authors synthesized Sn 3 Sb 2 S 6 thin films by an oblique angle deposition method, obtaining a direct band gap in the range of 1.44 eV to 1.66 eV and absorption coefficients from 10 5 to 10 6 cm −1 (Larbi et al, 2016). (SnS)m(Sb 2 S 3 )n thin films, including Sn 3 Sb 2 S 6 , were prepared by thermal evaporation using the glancing angle deposition technique (Abdelkader et al, 2018), the Sn 3 Sb 2 S 6 thin films showed direct band gap of 1.67 eV, absorption coefficients of 10 5 cm −1 and photocurrent of 25 mA/cm 2 for the sample with a thickness of approximately 250 nm. Bennaji et al (2019) obtained Sn 3 Sb 2 S 6 thin films via vacuum evaporation process followed by annealing process.…”
Section: Introductionmentioning
confidence: 99%
“…Glass (2 cm ×1 cm) were used as substrates for deposition of a copper fragments of 99.99% purity and 3×3 mm average size by vacuum thermal evaporation (Alcatel unit). The copper was deposited at different deposition angles α ranging from 0°to 85°(An illustration of the experiment is in [23]). The obtained thin films underwent thermal oxidation in air at a fixed temperature of 523 K and during 2 h.…”
Section: Methodsmentioning
confidence: 99%
“…Most cases of elaboration of such films are by vacuum thermal evaporation, sputtering, or e-beam. In previous works, it has been shown that the GLAD technique is able to create optical, electrical or magnetic anisotropy because of the highly oriented nanostructures [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…It is seen that optical dispersion dn/dλ of the film depends on both rotational speed and wavelength. The group velocity, Ug describing pulse propagation through an isotropic medium with undistorted shape is expressed as [33],…”
Section: Optical Dispersion Group and Phase Velocitymentioning
confidence: 99%